Periodontally accelerated osteogenic orthodontics combined with recombinant human bone morphogenetic protein-2: An outcome assessment - Rampalli Viswa Chandra; Madhukar Reddy Rachala; Koguru Madhavi; Prabhuraj Kambalyal; Aileni Amarender Reddy; Mir Hasan Ali (Wolters Kluwer Medknow Publications, 2019)
Context: Periodontally accelerated osteogenic orthodontics (PAOO) combines alveolar corticotomy, bone graft materials, and the application of orthodontic forces for rapid correction of malocclusions. Aims: The present study aims to primarily assess differences in orthodontic treatment duration, bone quality around corticotomy sites, postoperative healing, and subjective pain when corticotomy was done conventionally and with the placement of recombinant human bone morphogenetic protein-2 (rhBMP-2). Settings and Design: Thirty individuals participated in this study. Individuals were randomly assigned into each of the following experimental groups; C + BMP: Corticotomy with 0.5 μg/mL rhBMP-2 and C: Corticotomy only. Materials and Methods: Clinical parameters included recording the duration of the treatment period, visual analog scale scores and early wound healing index scores. The evaluation of bone density was performed at baseline, 3 months, and 6 months by using RVG. Statistical Analysis Used: Two-way analysis of variance and post hoc multiple comparison tests were used to compare data between test and control groups at different time points. Results: rhBMP-2 application was effective in reducing the overall treatment time and resulted in an increase in bone density around corticotomy sites at the end of the treatment period when compared to conventional corticotomy procedure. Placement of rhBMP-2 neither delayed wound healing nor affected participant pain scores. Conclusions: From this trial conducted over a period of 6 months, rhBMP-2 has the potential to function as a regenerative material in PAOO.